9514 1404 393
Answer:
7x +8y = 32
Step-by-step explanation:
Clear fractions and add the opposite of the x-term.
y = -7x/8 +4
8y = -7x +32 . . . . . multiply by 8
7x +8y = 32 . . . . . .add 7x
y = -2x + 9
y = 4x - 3
y is isolated in both equations, thus you may set the expressions (-2x + 9) and (4x - 3) equal to each other and solve for x.
-2x + 9 = 4x - 3
Subtract 9 from both sides.
-2x + 9 - 9 = 4x - 3 - 9
-2x = 4x - 12
Subtract 4x from both sides.
-2x - 4x = 4x - 12 - 4x
-6x = -12
Divide both sides by -6.
-6x/-6 = -12/-6
x = 2
Substitute 2 for x into one of the original equations to find y.
y = 4x - 3 (given)
y = 4(2) - 3 (substitute)
y = 8 - 3 (multiply)
y = 5 (subtract)
Plug x- and y-values into original equations to check work.
5 = -2(2) + 9
5 = - 4 + 9
5 = 5
5 = 4(2) - 3
5 = 8 - 3
5 = 5
Answer:
x = 2 and y = 5; (2, 5).
Removing the brackets gives 4a -2b +c -5c - a + 4b and then collect the like terms to get 3a + 2b - 4c
Answer: B) F(x) = √x and G(x) = 3x + 2
<u>Step-by-step explanation:</u>
The composite function G(F(x)) is when you replace every x-value in the G(x) function with the F(x) function.
![A)\ G(3x+2) = \sqrt{3x+2}\\\\B)\ G(\sqrt{x})=3(\sqrt{x})+2\quad =3\sqrt{x}+2\\\\C)\ G(\sqrt{x}+2) = 3\quad \text{there are no x-values in the G(x) function to replace}\\\\D) G(3\sqrt{x})=2\quad \text{there are no x-values in the G(x) function to replace}](https://tex.z-dn.net/?f=A%29%5C%20G%283x%2B2%29%20%3D%20%5Csqrt%7B3x%2B2%7D%5C%5C%5C%5CB%29%5C%20G%28%5Csqrt%7Bx%7D%29%3D3%28%5Csqrt%7Bx%7D%29%2B2%5Cquad%20%3D3%5Csqrt%7Bx%7D%2B2%5C%5C%5C%5CC%29%5C%20G%28%5Csqrt%7Bx%7D%2B2%29%20%3D%203%5Cquad%20%5Ctext%7Bthere%20are%20no%20x-values%20in%20the%20G%28x%29%20function%20to%20replace%7D%5C%5C%5C%5CD%29%20G%283%5Csqrt%7Bx%7D%29%3D2%5Cquad%20%5Ctext%7Bthere%20are%20no%20x-values%20in%20the%20G%28x%29%20function%20to%20replace%7D)
The only one that matches G(F(x)) = 3√x + 2 is OPTION B
Answer:
11/12
Step-by-step explanation:
8/12 vs 11/12 vs 10/12 vs 7/12